The impact of ABCB1 (rs1045642 and rs4148738) and CES1 (rs2244613) gene polymorphisms on dabigatran equilibrium peak concentration in patients after total knee arthroplasty - Sychev DA; Levanov AN; Shelekhova TV; Bochkov PO; Denisenko NP; Ryzhikova KA; Mirzaev KB; Grishina EA; Gavrilov MA; Ramenskaya GV; Kozlov AV; Bogoslovsky T (Dove Medical Press, 2018)
Dmitriy Alekseevich Sychev,1 Alexander Nikolaevich Levanov,2 Tatiana Vladimirovna Shelekhova,2 Pavel Olegovich Bochkov,3 Natalia Pavlovna Denisenko,4 Kristina Anatolyevna Ryzhikova,4 Karin Badavievich Mirzaev,3 Elena Anatolyevna Grishina,4 Mikhail Alekseevich Gavrilov,5 Galina Vladislavovna Ramenskaya,6 Aleksei Vladimirovich Kozlov,6 Tanya Bogoslovsky7 1Department of Clinical Pharmacology and Therapy, Russian Medical Academy of Continuous Professional Education, Moscow, Russia; 2Department of Occupational Pathology, Haematology and Clinical Pharmacology, Saratov State Medical University named after V.I. Razumovsky, Saratov, Russia; 3Department of Personalized Medicine, Research Center, Russian Medical Academy of Continuous Professional Education, Moscow, Russia; 4Department of Molecular Medicine, Research Center, Russian Medical Academy of Continuous Professional Education, Moscow, Russia; 5Department of Traumatology and Orthopedics, Research Institute of Traumatology, Orthopedics and Neurosurgery, Saratov State Medical University named after V.I. Razumovsky, Saratov, Russia; 6Department of A.P. Arzamastsev Pharmaceutical and Toxicological Chemistry, Sechenov First Moscow Medical State University, Moscow, Russia; 7Department of Neurology, Division of Clinical Neurosciences, Turku University Hospital, Turku, Finland Background: Non-vitamin K oral anticoagulants (NOACs) are commonly used for prophylaxis of venous thromboembolism (VTE) in orthopedic patients. Despite known safety and high potency of NOACs, potential interactions of NOACs with genetic polymorphisms are poorly understood. Dabigatran etexilate is one of the most commonly prescribed direct thrombin inhibitors for the prevention of VTE. The objectives of this study were to assess the effect of ABCB1 (rs1045642 and rs4148738) and CES1 (rs2244613) polymorphisms on dabigatran pharmacokinetics in patients after total knee arthroplasty. Patients and methods: A total of 60 patients, aged 37–81 years, who underwent surgery for knee replacement have been included in the study. VTE prophylaxis was conducted via administration of dabigatran etexilate 220 mg once daily. Genotyping for carrier state of polymorphic variants such as rs1045642 and rs4148738 of the ABCB1 gene and rs2244613 of the CES1 gene was carried out using real-time polymerase chain reaction (PCR). We also measured the peak and trough concentrations of plasma dabigatran by using high-performance liquid chromatography (HPLC). Results: Our study revealed that TT genotype of rs1045642 polymorphism of the ABCB1 gene was associated with higher dabigatran equilibrium peak concentrations and the higher risk of bleeding than the presence of CC genotype (p<0.008). There was no statistically significant genotype-dependent difference in the trough concentrations between rs1045642 and rs4148738 of the ABCB1 gene and rs2244613 of the CES1 gene. Conclusion: Our findings indicate that the polymorphisms of ABCB1 rs1045642 may have a prominent contribution to the safety of dabigatran in patients after knee surgery. Moreover, TT genotype may be associated with the higher risk of hemorrhagic complications in this population. There were no influence of polymorphism of ABCB1 rs4148738 and CES1 rs2244613 on dabigatran peak and through concentrations. Larger studies are needed to confirm our observations. Keywords: new oral anticoagulants, dabigatran, venous thromboembolism, ABCB1, CES1, pharmacogenetics